Toxicity and Safety Evaluation of Doxorubicin-Loaded Cockleshell-Derived Calcium Carbonate Nanoparticle in Dogs - Abubakar Danmaigoro; Gayathri Thevi Selvarajah; Mohd Hezmee Mohd Noor; Rozi Mahmud; Md Zuki Abu Bakar (Advances in Pharmacological Sciences)
Doxorubicin (DOX) is a potent anticancer agent with cytotoxic effects which limit its clinical usage. This effect is due to its nonselective nature causing injury to the cells as a result of reactive free oxygen radical’s release. Cockleshell-derived calcium carbonate nanoparticle (CS-CaCO3NP) is a pH-responsive carrier with targeted delivery potentials. This study aimed at evaluating the toxicity effects of repeated dose administration of DOX-loaded CS-CaCO3NP in healthy dogs. Fifteen dogs with an average body weight of 15 kg were randomized equally into 5 groups. Dogs were subjected to 5 doses at every 3-week interval with (i) normal saline, (ii) DOX, 30 mg/m2, and the experimental groups: CS-CaCO3NP-DOX at (iii) high dose, 50 mg/m2, (iv) clinical dose, 30 mg/m2, and (v) low dose, 20 mg/m2. Radiographs, electrocardiography, and blood samples were collected before every treatment for haematology, serum biochemistry, and cardiac injury assessment. Heart and kidney tissues were harvested after euthanasia for histological and ultrastructural evaluation. The cumulative dose of DOX 150 mg/m2 over 15 weeks revealed significant effects on body weight, blood cells, functional enzymes, and cardiac injury biomarkers with alterations in electrocardiogram, myocardium, and renal tissue morphology. However, the dogs given CS-CaCO3NP-DOX 150 mg/m2 and below did not show any significant change in toxicity biomarker as compared to those given normal saline. The study confirmed the safety of repeated dose administration of CS-CaCO3NP-DOX (30 mg/m2) for 5 cycles in dogs. This finding offers opportunity to dogs with cancer that might require long-term administration of DOX without adverse effects.